Prognostic Implications of Bronchoalveolar Fluid Analysis in Ventilator-Associated Pneumonia: An Observational Cohort Study - Walid M. Kamel; Ahmad S. Fayed; Raef H. Emam; Ashraf W. Andraos (Egyptian Journal of Critical Care Medicine)
Abstract Background Ventilator-associated pneumonia (VAP) is one of the most frequent infections with high mortality rates in intensive care units (ICUs) and the prediction of outcome is paramount in the decision-making process. Objective To assess the prognostic value of cellular analysis of bronchoalveolar lavage fluid (BAL) in the prediction of mechanical ventilation (MV) weaning and mortality during VAP episodes in ICU patients. Methods This study was a prospective observational cohort study. Sixty patients who were admitted to critical care department at Cairo university hospitals and developed VAP, were included in the study consecutively. Clinical and laboratory data were recorded on admission as well as CPIS, PSI, PIRO, and IBMP-10 scores on the day of the diagnosis of VAP. All patients had bronchoalveolar lavage after diagnosis of VAP was established. The BALF was sent for cellular analysis (total and differential leucocytic count). Results From a total of 60 patients with VAP, 51.7% were males, the age was 59.6 ± 17.5 years. Mortality rate was 86.7% and failed weaning was recorded in 53 patients (88.3%). Survivors and non-survivors had no significant differences, apart from higher PIRO scores in non-survivors. Bronchoscopic fluid analysis showed higher TLC, neutrophils, lymphocytes, and macrophages in those who failed mechanical ventilation. Neutrophils in BAL > 170/cc showed 60.4% sensitivity and 71.4% specificity for predicting failed MV weaning. Lymphocytes in BAL > 45/cc showed 56.6% sensitivity and 71.4% specificity for predicting failed MV weaning. Conclusion Bronchial lavage cellular fluid analysis could bear prognostic information in ventilator associated pneumonia. Increased bronchoalveolar lavage neutrophils and lymphocytes showed increased rates of mortality and weaning failure in ventilator associated pneumonia.